Social Critique within the Kabhanti Modero Tradition: An Interactional Development Communication Model among the Muna Indigenous Community - Fetni, Fetni; Fait, Taslim; Mardiana, Mardiana; Ashari, Saepul (CV. Social Politic Genius (SIGn), 2025)
The top-down structural development communication paradigm often leads to communication impasses and fails to accommodate grassroots aspirations. Amidst this bureaucratic paralysis, the kabhanti modero oral tradition among the Muna indigenous community in Southeast Sulawesi Province emerges not merely as an entertainment medium but as a dialogic space that actively responds to development failures. This study aims to examine the mechanisms of social critique encapsulated within kabhanti modero lyrics and to analyze the operationalization of this tradition as an interactional development communication model. This research employed a qualitative case study design, using participatory observation, in-depth interviews with core communicators and customary leaders, and documentation of sacred life-cycle rites. The research results demonstrated that the chanted pantun lyrics serve as symbolic interaction instruments to articulate the community’s real grievances regarding infrastructure failures through polite yet politically coercive metaphors. The operationalization of this critique delivery is executed through a centralized circular formation that dismantles spatial barriers between the lay public and government elites. Furthermore, the existence of a conflict mitigation pact, internal message curation mechanisms, the involvement of customary authorities, and collective validation from the audience provide absolute social legitimacy for demands to improve government performance. This study concludes that kabhanti modero constitutes a tangible social control instrument and a highly effective form of sociological sanction. Therefore, local governments are recommended to integrate this cultural dialogic space into development planning deliberations to minimize elitist information bias.